Thyroid Surgery - Testini, Mario; Gurrado, Angela (Updates in Surgery,, 2024)
This open access book on thyroid surgery has been authored by an international team of contributors who present a comprehensive understanding of both benign and malignant thyroid disorders. It also outlines an interdisciplinary approach to their surgical management that reflects the latest changes in surgical techniques. The book reviews the most up-to-date literature available on thyroid surgery and presents it in a concise manner for use in clinical practice. For each thyroid disorder, the book covers etiology, clinical manifestations, diagnostic and localization procedures, as well as surgical and non-surgical treatment options. The operating techniques and postoperative management are explained in detail, while the benefits, risks, controversial issues, and cost-effectiveness of each approach are reviewed. To aid in the understanding of complex information, the book features drawings and photographs. Written in an easy-to-understand style, the book includes tables and diagrams that highlight best practices and current guidelines, as well as self-assessment material at the end of each section. It serves as an ideal resource for all levels of surgical experience, from a practical reference for endocrine surgeons to a perfect companion for students and residents.